The protective role of virgin coconut oil on the alloxan-induced oxidative stress in the liver, kidneys and heart of diabetic rats. Issue 4 (28th March 2019) - Đurašević, Siniša; Jasnić, Nebojša; Prokić, Marko; Grigorov, Ilijana; Martinović, Vesna; Đorđević, Jelena; Pavlović, Slađan
Abstract : Our results show that VCO supplementation ameliorates some toxic effects of alloxan induced diabetes, and that the changes are tissue specific. Abstract : The aim of this study was to investigate the potential protective effect of virgin coconut oil (VCO) on oxidative stress parameters in the liver, kidneys and heart of alloxan-induced (150 mg kg −1 i.p. −1 ) diabetes in rats. Our results showed that daily supplementation of VCO (20% of food) for 16 weeks significantly ( p < 0.05) ameliorates some deleterious effects caused by alloxan. VCO reduced the diabetes-related increase in food (82.15 ± 1.49 vs . 145.51 ± 4.81 g per kg b.m. per day) and water (305.49 ± 6.09 vs . 583.98 ± 14.80 mL per kg b.m. per day) intake, and the decrease in the body mass gain (0.56 ± 0.16 vs . −2.13 ± 0.49 g per 100 g b.m. per week). In all three tissues, diabetes caused an increase in the concentration of total glutathione and sulfhydryl groups, and catalase and glutathione S -transferase activities, without changes in superoxide dismutase activity. Glutathione peroxidase activity was increased in the kidneys and heart, but not in the liver of the diabetic animals, while glutathione reductase activity was increased in the liver and the kidneys, and not in the heart. The simultaneous VCO supplementation increased the concentration of the sulfhydryl group in all three tissues of diabetic animals and decreased the glutathione S -transferase activity and glutathione concentration, without affecting the glutathione reductase activity. In the liver of diabetic animals it decreased superoxide dismutase, catalase and glutathione peroxidase activities, in the heart catalase and glutathione peroxidase activities, and in the kidney catalase activity only. The results of canonical discriminant analysis of oxidative stress parameters revealed that VCO exerts its effects in a tissue-specific manner.